Elevated resting heart rate is associated with increased radiographic severity of knee but not hand joints - Choi, Sung-Eun; Xu, Haimuzi; Kang, Ji-Hyoun; Park, Dong-Jin; Kweon, Sun-Seog; Lee, Young-Hoon; Kim, Hye-Yeon; Lee, Jung-Kil; Shin, Min-Ho; Lee, Shin-Seok (Scientific reports, 2021)
Although the resting heart rate (RHR) predicts the clinical outcomes of cardiovascular disease, chronic obstructive lung disease, diabetes mellitus, and the risk of cancer, its role in patients with musculoskeletal diseases, such as osteoarthritis (OA), remains unclear. We explored the association of the RHR with the extents of radiographic changes in the knees and hands of 2369 subjects from the Dong-gu Study. The radiographic hand and knee joint findings were graded semi-quantitatively; we calculated total hand and knee joint scores. Multiple linear regression was performed to examine the associations between the RHR and the radiographic characteristics of these joints. For the knee joints, the RHR was associated positively with the total ( p < 0.01), osteophyte ( p < 0.01), joint space narrowing (JSN; p < 0.01), and tibial attrition ( p = 0.02) scores after adjustment for age, sex, body mass index, smoking status, alcohol consumption, educational and physical activity levels, and comorbidities. For the hand joints, the RHR was associated positively with the JSN ( p = 0.01) and subchondral cyst ( p < 0.01) scores after such adjustment. The RHR was not associated with the total, osteophyte, sclerosis, erosion, or malalignment score for the hand joints. This study is the first to reveal an association between the RHR and the radiographic severity of knee, but not hand, OA.